CDCP1-targeting ADC outperforms standard therapies in Ras-mutant pancreatic cancer - Yun Jung Um; Hee-Dong Noh; Jin Gu Cho; Han-Jik Ko; Tae Min Wi; Jin-Ock Kim; Sang Gyu Park (Molecular Therapy: Oncology)
RAS mutations are found in 10%–30% of various cancers and in up to 90% of pancreatic cancers, where they are associated with aggressive phenotypes, poor prognosis, and reduced overall survival. CUB domain containing protein 1 (CDCP1), a transcriptional target of activated RAS, is implicated in these cancers irrespective of the specific RAS mutation. Given the limited effectiveness of small-molecule inhibitors against mutant Ras-driven cancers, we developed a CDCP1-targeting antibody-drug conjugate (ADC). In this study, we demonstrate that CDCP1 overexpression significantly correlates with RAS mutations in pancreatic cancer. We generated and characterized a CDCP1-specific monoclonal antibody, 2G10, and conjugated it to the topoisomerase II inhibitor, PNU159682, to produce 2G10-PNU159682. The anti-tumor activity of this ADC was evaluated in vitro and in vivo using pancreatic cancer cell lines. 2G10-PNU159682 exhibited superior efficacy compared to MRTX1133 and sotorasib in G12D- and G12C-mutant cell lines. In a mouse xenograft model, 2G10-PNU159682 demonstrated robust anti-tumor activity against RAS-mutant pancreatic cancers, outperforming gemcitabine and FOLFIRINOX and achieving complete tumor remission for up to 100 days—even following relapse after standard chemotherapy. These findings support the potential of 2G10-PNU159682 as a promising therapeutic candidate for the treatment of Ras-mutant cancers.